Factors Influencing Behavioural Intention to Adopt e-AgriFinance among the Farmers in Sarawak - Omar, Quistina Binti (Curtin University, 2020)
Digital finance offers transformational solutions to the chronic challenges in the agriculture value chain. While agriculture apps have been well developed and widely used in some developed and developing countries, there exist no mobile apps that incorporate digital finance and agriculture in the local context, especially in Sarawak. Therefore, this study aims to investigate the behavioural intention of farmers in Sarawak to adopt digital finance in the agriculture sector or e-AgriFinance.